A method for preparing a Ti-Al-C-based MAX phase ceramic-metal composite coating on a titanium alloy surface

By preparing a Ti-Al-C MAX phase ceramic-metal composite coating on the surface of titanium alloy and constructing a double-barrier structure using a slurry sintering process, the problems of uneven coating thickness and easy failure were solved, achieving excellent protective performance and long-life coating under high temperature environment.

CN122303786APending Publication Date: 2026-06-30NANTONG SHIPPING COLLEGE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610547864.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-23
Publication Date
2026-06-30

AI Technical Summary

Technical Problem

Existing titanium alloy surface modification technologies suffer from uneven coating thickness and susceptibility to failure. In particular, oxide layer failure occurs at high temperatures, leading to material performance degradation and making it difficult to meet the high-temperature application requirements of high thrust-to-weight ratio engines.

Method used

A Ti-Al-C MAX phase ceramic-metal composite coating was prepared on the surface of titanium alloy using a slurry sintering process. The coating consists of an outer Ti-Al intermetallic compound phase and an inner Ti-Al-C MAX phase, forming a dual-barrier synergistic protection structure. The coating uniformity and thickness controllability are achieved by controlling the slurry coating thickness.

Benefits of technology

It significantly improves the coating's oxidation and corrosion resistance, solves the problem of coating failure in high-temperature environments, is suitable for complex-shaped workpieces, reduces production costs, and increases the coating's service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122303786A_ABST
    Figure CN122303786A_ABST
Patent Text Reader

Abstract

This invention discloses a method for preparing a Ti-Al-C MAX phase ceramic-metal composite coating on the surface of titanium alloys, belonging to the field of titanium alloy surface coatings. The coating exhibits a structure of an outer Ti-Al intermetallic compound phase and an inner Ti-Al-C MAX phase. The outer layer impedes the diffusion of external oxygen and corrosive media inwards; the inner layer effectively inhibits elemental interdiffusion between the substrate and the coating, and further hinders the diffusion and penetration of oxygen and corrosive media. The specific method involves: preparing carbon nanoparticle slurry and Al slurry separately; uniformly brushing the carbon nanoparticle slurry onto the surface of a pretreated titanium alloy workpiece and vacuum drying it; then coating the surface with Al slurry and vacuum drying it again; finally, placing the workpiece in a vacuum heat treatment furnace, holding it at that temperature for a certain time, and then cooling it with the furnace to obtain the composite coating. The composite coating prepared by this process has good thermal stability, good bonding with the substrate, low cost, and wide applicability, and can effectively extend the service life of titanium alloy workpieces in high-temperature and complex environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of titanium alloy surface coating technology, specifically to a method for preparing a Ti-Al-C MAX phase ceramic-metal composite coating on the surface of a titanium alloy. Background Technology

[0002] As the core power plant of aircraft, aero engines require key components to withstand extreme stress and high-temperature environments while meeting high thrust-to-weight ratio design requirements. Titanium alloys, with their excellent properties such as low density, high specific strength, and resistance to high-temperature corrosion, have become the preferred material for important components such as engine compressor disks, blades, rotors, and casings. However, with the development of high thrust-to-weight ratio engines and high Mach number aircraft, titanium alloys face severe challenges at high temperatures—their oxide layer transforms into a non-protective state at high temperatures, leading to material performance degradation. Currently, the short-term maximum operating temperature of advanced high-temperature titanium alloys in China is still limited to below 800℃. Therefore, improving their high-temperature performance through surface modification technology while maintaining the properties of the base material is of significant engineering importance.

[0003] In the field of titanium alloy surface modification, filler plating and hot-dip galvanizing are widely used due to their economic efficiency and practicality, as both can form thick coatings and achieve good interfacial bonding. However, filler plating suffers from drawbacks such as long process cycles and difficulty in controlling coating thickness, while hot-dip galvanizing is prone to uneven coating thickness due to surface tension. In contrast, slurry sintering allows for flexible customization of coating thickness by adjusting the slurry dosage and can obtain uniform coatings without being affected by surface tension, demonstrating unique process advantages.

[0004] Ti-Al coatings have significant application value in the surface modification of titanium alloys, and can significantly improve the high-temperature performance of the base material. However, during long-term use, especially in hot corrosion environments, the protective performance of Ti-Al coatings is easily damaged by accelerated oxidation, leading to gradual coating failure and ultimately loss of protective efficacy against the titanium alloy substrate. This problem severely restricts its application expansion under extreme high-temperature conditions.

[0005] MAX phases, as a novel class of ternary layered compounds, combine the excellent properties of both metals and ceramics: possessing the high electrical and thermal conductivity, good machinability, and thermal shock resistance of metallic materials, and the high modulus, high-temperature oxidation resistance, and corrosion resistance of ceramic materials. Their unique nanolayered crystal structure endows them with self-lubricating properties and high toughness, making them highly promising machinable ceramic materials. Typical Ti-Al-C MAX phase compounds, Ti2AlC and Ti3AlC2, integrate the high electrical conductivity and high fracture toughness of metals with the high strength and excellent high-temperature performance of ceramics, while maintaining good machinability, showing broad prospects in engineering applications. Applying these materials to the surface modification of titanium alloys can significantly improve the high-temperature oxidation resistance and thermal corrosion resistance of the matrix material, providing a new solution to overcome the bottlenecks in high-temperature applications of titanium alloys.

[0006] Chinese patent CN113430479B discloses a Ti-Al-Si-C coating modified with carbon nanomaterials on the surface of titanium and titanium alloys, and its preparation method. Although this method obtains a functional coating containing the Ti3AlC2 phase on the surface of titanium and titanium alloy substrates through hot-dip plating, it still has significant technical bottlenecks and limitations in engineering applications. On the one hand, the Ti3AlC2 coating has inherent defects such as thinness and poor controllability: during large-scale preparation and long-term use, an excessively thin coating is prone to premature depletion and local failure, and uncontrollable thickness will aggravate the thermal stress mismatch between the coating and the substrate, inducing thermal stress cracks and interfacial bonding failure. On the other hand, compared with the slurry sintering process, the surface tension of the molten plating solution during hot-dip plating easily affects its wetting and spreading on the substrate surface, resulting in a more prominent problem of uneven coating thickness, making it difficult to meet the quality consistency requirements of large-scale preparation.

[0007] In view of this, in-depth research was conducted on the above issues, which led to the creation of this case. Summary of the Invention

[0008] The present invention aims to provide a method for preparing a Ti-Al-C MAX phase ceramic-metal composite coating on the surface of titanium alloys. This method effectively overcomes the process defects of filler plating and hot-dip plating, while fully integrating the advantages of Ti-Al intermetallic compound phases and Ti-Al-C MAX phases. The prepared coating exhibits excellent thermal stability, high density, and superior oxidation and corrosion resistance. Furthermore, this preparation method is not limited by the shape of the workpiece, is simple to operate, highly efficient, low in cost, and has a wide range of applications.

[0009] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a Ti-Al-C MAX phase ceramic-metal composite coating on the surface of a titanium alloy, comprising the following steps: Step 1: Mix carbon nanomaterials with water-soluble solvent, dispersant, and binder to prepare carbon nanomaterial slurry; Step 2: Pre-treat the surface of the titanium alloy workpiece; Step 3: Coat the carbon nanoparticle slurry obtained in Step 1 evenly onto the surface of the workpiece obtained in Step 2, and dry it; Step 4: Mix Al powder with binder aqueous solution to prepare Al slurry; Step 5: Apply the Al slurry obtained in Step 4 evenly to the surface of the coating obtained in Step 3, and let it dry; Step 6: Under an inert atmosphere, the workpiece obtained in Step 5 is sintered at 880℃-920℃ for 3-7 hours and then cooled in the furnace to obtain a Ti-Al-C MAX phase ceramic-metal composite coating on the surface of the titanium alloy.

[0010] Preferably, the carbon nanomaterial slurry in step 1 is composed of the following components by mass percentage: 40 wt% carbon nanomaterial, 2 wt% dispersant, 5 wt% binder, and the balance being water solvent.

[0011] Preferably, in step 1, the titanium alloy is Ti65 alloy; the carbon nanomaterial is carbon nanotube; the dispersant is polyvinylpyrrolidone; and the binder is carboxymethyl cellulose.

[0012] Preferably, the pretreatment in step 2 includes grinding the surface of the titanium alloy workpiece to make it smooth, removing the surface oxide scale and oil stains by acid pickling and alkaline washing, and then drying it in a vacuum drying oven.

[0013] Preferably, the coating thickness of the carbon nanoparticle slurry in step 3 is 5-20 μm.

[0014] Preferably, in step 4, the Al content of the Al powder is 99.9% or higher; the binder aqueous solution is a 5 wt% polyvinyl alcohol aqueous solution; and the mass ratio of the Al powder to the binder aqueous solution is 1:1.

[0015] Preferably, the inert atmosphere in step 6 is argon.

[0016] Preferably, the sintering temperature in step 6 is 900℃ and the holding time is 5 hours.

[0017] The present invention also provides a Ti-Al-C MAX phase ceramic-metal composite coating prepared by the above method, wherein the composite coating is composed of an outer Ti-Al intermetallic compound phase and an inner Ti-Al-C MAX phase.

[0018] Preferably, the outer Ti-Al intermetallic compound phase serves as the first barrier against high-temperature oxidation corrosion, and the inner Ti-Al-C MAX phase serves as the second barrier against high-temperature oxidation corrosion and to inhibit elemental interdiffusion, forming a dual-barrier synergistic protection structure.

[0019] Compared with existing technologies, the advantages of a method for preparing a Ti-Al-C MAX phase ceramic-metal composite coating on the surface of titanium alloys are: 1. The coating system constructed using slurry sintering has significant advantages in process adaptability: on the one hand, the process is simple to operate and is not limited by the complex geometry of titanium alloy workpieces, and can achieve uniform coating of the entire surface; on the other hand, by precisely controlling the amount of slurry, the coating thickness can be customized as needed, avoiding the long cycle loss of filler plating and the material waste of hot-dip plating, and reducing production costs. 2. This invention is the first to propose a composite coating on a titanium alloy substrate, combining an inner Ti-Al-C MAX phase layer and an outer Ti-Al intermetallic compound phase. The outer layer acts as the first barrier against high-temperature oxidation and hot corrosion, utilizing the Ti-Al intermetallic compound to impede external oxygen and corrosive media. The inner layer, through the Ti-Al-C MAX phase, effectively inhibits elemental interdiffusion between the substrate and the coating, and serves as a second protective layer against high-temperature oxidation and corrosion, forming a "dual-barrier" synergistic protection mechanism. This structural design solves the structural failure problem of existing Ti-Al coatings caused by elemental interdiffusion, significantly improving the service life of the coating in high-temperature and complex environments. 3. Based on the controllability advantage of the slurry sintering process, by adjusting the coating thickness parameter of the carbon nanomaterial slurry, the thickness ratio of the inner layer of Ti-Al-C system MAX phase and the outer layer of Ti-Al intermetallic compound in the composite coating can be precisely controlled, so as to realize the optimized design of coating structure for different application environments. 4. Compared with the MAX phase coating prepared by the existing hot-dip plating process, the composite coating prepared by the present invention has controllable thickness and good uniformity, avoiding the micro-crack problem induced by thermal stress mismatch; compared with the existing filler plating process, the present invention has a short process cycle and high efficiency, and is suitable for large-scale production. Attached Figure Description

[0020] Figure 1 The image shows the microstructure of the Ti-Al coating obtained in Comparative Example 2. Figure 2 This is a cross-sectional microstructure image of the composite coating obtained in Example 1; Figure 3 This is a cross-sectional microstructure image of the composite coating obtained in Example 2; Figure 4 The image shows the X-ray diffraction pattern of the composite coating obtained in Example 1 near the substrate. Figure 5 The oxidation weight gain curves of the workpieces obtained in Comparative Example 1, Comparative Example 2, and Example 1 in an air environment at 800°C are shown. Figure 6The graph shows the corrosion weight gain curves of the workpieces obtained from Comparative Example 1, Comparative Example 2, and Example 1 in an environment of 75wt.% Na2SO4 + 25wt.% NaCl at 800℃. Detailed Implementation

[0021] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] Please see Figure 1-6 The present invention provides the following technical solutions: Comparative Example 1 Ti65 alloy plates (10mm × 10mm × 5mm) were selected and placed in an air environment at 800℃ and in a mixed salt environment consisting of 75wt.% Na2SO4 + 25wt.% NaCl. Samples were taken from each environment at regular time intervals (5 hours, 10 hours, 20 hours, 50 hours, and 100 hours) to measure the oxidation weight gain in the air environment and the corrosion weight gain in the 75wt.% Na2SO4 + 25wt.% NaCl mixed salt environment. The final oxidation weight gain curves and corrosion weight gain curves are shown below. Figure 5 and Figure 6 As shown.

[0023] Comparative Example 2 (1) Select a Ti65 alloy plate (size is 10mm×10mm×5mm), and polish the surface with 240 grit, 600 grit and 1000 grit sandpaper in sequence. Remove the oxide scale and oil stains on the surface by acid washing and alkali washing. Then dry it in a vacuum drying oven at 80℃ for 2 hours and set aside for use. (2) Al powder with an Al content of 99.99% and an aqueous solution of 5 wt% polyvinyl alcohol were mixed at a mass ratio of 1:1, and then the mixture was stirred for 30 minutes at a speed of 3000 r / min using a high shear mixer to obtain an Al slurry. (3) Take the Al slurry prepared in step 2 and apply it evenly to the surface of the workpiece obtained in step 1. The coating thickness is about 100 μm. Then dry it in a vacuum drying oven at 80°C for 2 hours and set aside for later use. (4) The vacuum heat treatment furnace is heated to 900°C. Under argon protection, the workpiece obtained in step 3 is placed in the heat treatment furnace and kept at the temperature for 5 hours. Finally, it is cooled with the furnace to obtain the Ti-Al coating on the surface of Ti65 alloy. (5) The workpieces obtained in step 4 were placed in an air environment at 800℃ and in a mixed salt environment consisting of 75wt.% Na2SO4 + 25wt.% NaCl, respectively. At regular intervals (5 hours, 10 hours, 20 hours, 50 hours, and 100 hours), a sample was taken from the corresponding environment, and its oxidation weight gain in the air environment and corrosion weight gain in the 75wt.% Na2SO4 + 25wt.% NaCl mixed salt environment were measured. The final oxidation weight gain curve and corrosion weight gain curve are shown below. Figure 5 and Figure 6 As shown. Example 1

[0024] (1) Dissolve 40 wt% carbon nanotubes (average diameter 10-20 nm, length 5-15 μm) in an aqueous solvent, add 2 wt% polyvinylpyrrolidone dispersant and ultrasonically disperse for 30 minutes (ultrasonic power 500W), then add 5 wt% carboxymethyl cellulose binder and magnetically stir for 2 hours to obtain carbon nanotube slurry. (2) Select a Ti65 alloy plate (10mm×10mm×5mm in size), and polish the surface with 240 grit, 600 grit and 1000 grit sandpaper in sequence. Remove the oxide scale and oil stains on the surface by acid washing and alkali washing. Then dry it in a vacuum drying oven at 80℃ for 2 hours and set aside for use. (3) Take the carbon nanomaterial slurry prepared in step 1 and apply it evenly to the surface of the workpiece obtained in step 2. The coating thickness is about 5 μm. Then dry it in a vacuum drying oven at 80°C for 2 hours and set aside for later use. (4) Al powder with an Al content of 99.99% and an aqueous solution of 5 wt% polyvinyl alcohol were mixed at a mass ratio of 1:1, and then the mixture was stirred for 30 minutes at a speed of 3000 r / min using a high shear mixer to obtain an Al slurry. (5) Take the Al slurry prepared in step 4 and apply it evenly to the surface of the workpiece obtained in step 3. The coating thickness is 100 μm. Then dry it in a vacuum drying oven at 80°C for 2 hours and set aside for later use. (6) The vacuum heat treatment furnace is heated to 900°C. Under argon protection, the workpiece obtained in step 5 is placed in the heat treatment furnace and kept at the temperature for 5 hours. Finally, it is cooled with the furnace to obtain a Ti65 alloy surface containing a Ti-Al-C MAX phase ceramic metal composite coating. (7) The workpieces obtained in step 6 were placed in an air environment at 800℃ and in a mixed salt environment consisting of 75wt.% Na2SO4 + 25wt.% NaCl, respectively. At regular intervals (5 hours, 10 hours, 20 hours, 50 hours, and 100 hours), a sample was taken from the corresponding environment, and its oxidation weight gain in the air environment and corrosion weight gain in the 75wt.% Na2SO4 + 25wt.% NaCl mixed salt environment were measured. The final oxidation weight gain curves and corrosion weight gain curves are shown below. Figure 5 and Figure 6 As shown. Example 2

[0025] (1) Dissolve 40 wt% carbon nanotubes (average diameter 10-20 nm, length 5-15 μm) in an aqueous solvent, add 2 wt% polyvinylpyrrolidone dispersant and ultrasonically disperse for 30 minutes (ultrasonic power 500W), then add 5 wt% carboxymethyl cellulose binder, magnetically stir for 2 hours and filter to obtain carbon nanotube slurry. (2) Select a Ti65 alloy plate (10mm×10mm×5mm in size), and polish the surface with 240 grit, 600 grit and 1000 grit sandpaper in sequence. Remove the oxide scale and oil stains on the surface by acid washing and alkali washing. Then dry it in a vacuum drying oven at 80℃ for 2 hours and set aside for use. (3) Take the carbon nanoparticle slurry prepared in step 1 and apply it evenly to the surface of the workpiece obtained in step 2. The coating thickness is about 20 μm. Then dry it in a vacuum drying oven at 80°C for 2 hours and set aside for later use. (4) Al powder with an Al content of 99.99% and an aqueous solution of 5 wt% polyvinyl alcohol were mixed at a mass ratio of 1:1, and then the mixture was stirred for 30 minutes at a speed of 3000 r / min using a high shear mixer to obtain an Al slurry. (5) Take the Al slurry prepared in step 4 and apply it evenly to the surface of the workpiece obtained in step 3. The coating thickness is 100 μm. Then dry it in a vacuum drying oven at 80°C for 2 hours and set aside for later use. (6) The vacuum heat treatment furnace is heated to 900°C. Under argon protection, the workpiece obtained in step 5 is placed in the heat treatment furnace and kept at the temperature for 5 hours. Finally, it is cooled with the furnace to obtain a Ti-Al-C MAX phase ceramic metal composite coating on the surface of Ti65 alloy.

[0026] Results Analysis 1. Microstructural Morphology Analysis The microstructure morphology of the Ti-Al coating prepared in Comparative Example 2 is as follows: Figure 1 As shown, the coating structure is relatively dense, but there are a few microcracks.

[0027] The cross-sectional microstructure morphology of the composite coating obtained in Example 1 is as follows: Figure 2 As shown, the coating adheres well to the substrate, with a clear interface and no cracks or pores. The coating exhibits a distinct bilayer structure: the outer layer is a Ti-Al intermetallic compound phase, and the inner layer is a Ti-Al-C MAX phase.

[0028] The cross-sectional microstructure morphology of the composite coating obtained in Example 2 is as follows: Figure 3 As shown, the coating also exhibits a clear bilayer structure. Due to the increase in the coating thickness of the carbon nanoparticle slurry to 20 μm, the thickness of the inner Ti-Al-C MAX phase increases accordingly, verifying that the method of the present invention can achieve precise control of the coating structure by adjusting the coating thickness of the slurry.

[0029] 2. Phase composition analysis The X-ray diffraction pattern of the composite coating near the substrate obtained in Example 1 is as follows: Figure 4 As shown in the figure, the diffraction peaks of Ti2AlC are clearly displayed, confirming that the inner layer is a Ti-Al-C MAX phase structure. Simultaneously, a Ti-Al intermetallic compound phase was detected, consistent with the bilayer structure analysis results.

[0030] 3. Analysis of high-temperature oxidation resistance Figure 5 The graphs show the oxidation weight gain of Comparative Example 1 (uncoated Ti65 alloy), Comparative Example 2 (Ti-Al coating), and Example 1 (composite coating) in air at 800°C. The results show: The uncoated Ti65 alloy (Comparative Example 1) showed the most significant oxidation weight gain throughout the entire test period, and maintained a relatively fast weight gain rate over time. The Ti-Al coated sample (Comparative Example 2) showed a significant reduction in oxidation weight gain, indicating that the Ti-Al coating has a certain antioxidant protection effect. The composite coated sample (Example 1) showed the least oxidation weight gain, and its weight gain curve was the flattest throughout the entire test period, indicating that its antioxidant performance was significantly better than that of Comparative Example 1 and Comparative Example 2, verifying the synergistic protective effect of the "dual barrier" structure.

[0031] 4. Analysis of heat and corrosion resistance Figure 6 The graph shows the corrosion weight gain curves of Comparative Example 1, Comparative Example 2, and Example 1 in a mixed salt environment of 75 wt.% Na2SO4 + 25 wt.% NaCl at 800℃. The results show: The uncoated Ti65 alloy (Comparative Example 1) showed significant corrosion weight gain in the early stage of the test and maintained a relatively fast corrosion weight gain rate over time; the corrosion weight gain of the Ti-Al coated sample (Comparative Example 2) was significantly reduced, showing better heat corrosion resistance; the composite coated sample (Example 1) had the smallest corrosion weight gain and the flattest weight gain curve throughout the entire test period, and its heat corrosion resistance was significantly better than that of Comparative Example 1 and Comparative Example 2.

[0032] 5. Summary of Results The above results demonstrate that the composite coating prepared in this invention (Example 1) significantly outperforms the uncoated titanium alloy (Comparative Example 1) and the single Ti-Al coating (Comparative Example 2) in both oxidation resistance and thermal corrosion resistance. This is mainly attributed to the unique "double barrier" structure of this invention: the outer layer blocks the diffusion of external oxygen and corrosive media inward; the inner layer effectively inhibits the interdiffusion of elements between the substrate and the coating, and further hinders the diffusion and penetration of oxygen and corrosive media. The synergistic effect of the inner and outer layers significantly improves the protective performance of the coating in high-temperature and complex environments.

[0033] Furthermore, by comparing the coating structures of Example 1 and Example 2, it can be seen that the method of the present invention can achieve precise control of the thickness ratio of the inner and outer layers of the composite coating by adjusting the coating thickness of the carbon nanomaterial slurry, thereby meeting the personalized needs of different application environments for the coating structure.

[0034] Contents not described in detail in this specification are prior art known to those skilled in the art. Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a Ti-Al-C MAX phase ceramic-metal composite coating on the surface of a titanium alloy, characterized in that, Includes the following steps: Step 1: Mix carbon nanomaterials with water-soluble solvent, dispersant, and binder to prepare carbon nanomaterial slurry; Step 2: Pre-treat the surface of the titanium alloy workpiece; Step 3: Coat the carbon nanoparticle slurry obtained in Step 1 evenly onto the surface of the workpiece obtained in Step 2, and dry it; Step 4: Mix Al powder with binder aqueous solution to prepare Al slurry; Step 5: Apply the Al slurry obtained in Step 4 evenly to the surface of the coating obtained in Step 3, and let it dry; Step 6: Under an inert atmosphere, the workpiece obtained in Step 5 is sintered at 880℃-920℃ for 3-7 hours and then cooled in the furnace to obtain a Ti-Al-C MAX phase ceramic-metal composite coating on the surface of the titanium alloy.

2. The method for preparing a Ti-Al-C MAX phase ceramic-metal composite coating on the surface of a titanium alloy according to claim 1, characterized in that: The carbon nanomaterial slurry in step 1 is composed of the following components by mass percentage: 40 wt% carbon nanomaterial, 2 wt% dispersant, 5 wt% binder, and the balance being water solvent.

3. The method for preparing a Ti-Al-C MAX phase ceramic-metal composite coating on the surface of a titanium alloy according to claim 1, characterized in that: In step 1, the titanium alloy is Ti65 alloy; the carbon nanomaterial is carbon nanotube; the dispersant is polyvinylpyrrolidone; and the binder is carboxymethyl cellulose.

4. The method for preparing a Ti-Al-C MAX phase ceramic-metal composite coating on the surface of a titanium alloy according to claim 1, characterized in that: The pretreatment in step 2 includes grinding the surface of the titanium alloy workpiece to make it smooth, removing the surface oxide scale and oil stains by acid pickling and alkaline washing, and then drying it in a vacuum drying oven.

5. The method for preparing a Ti-Al-C MAX phase ceramic-metal composite coating on the surface of a titanium alloy according to claim 1, characterized in that: The coating thickness of the carbon nanoparticle slurry in step 3 is 5-20 μm.

6. The method for preparing a Ti-Al-C MAX phase ceramic-metal composite coating on the surface of a titanium alloy according to claim 1, characterized in that: In step 4, the Al content of the Al powder is 99.9% or higher; the binder aqueous solution is a 5 wt% polyvinyl alcohol aqueous solution; and the mass ratio of the Al powder to the binder aqueous solution is 1:

1.

7. The method for preparing a Ti-Al-C MAX phase ceramic-metal composite coating on the surface of a titanium alloy according to claim 1, characterized in that: In step 6, the inert atmosphere is either argon or helium.

8. The method for preparing a Ti-Al-C MAX phase ceramic-metal composite coating on the surface of a titanium alloy according to claim 1, characterized in that: In step 6, the sintering temperature is 900℃ and the holding time is 5 hours.

9. A Ti-Al-C MAX phase ceramic-metal composite coating prepared by the method according to any one of claims 1-8, characterized in that: The composite coating consists of an outer Ti-Al intermetallic compound phase and an inner Ti-Al-C MAX phase.

10. The Ti-Al-C MAX phase ceramic-metal composite coating according to claim 9, characterized in that, The outer Ti-Al intermetallic compound phase serves as the first barrier against high-temperature oxidation corrosion, while the inner Ti-Al-C MAX phase serves as the second barrier against high-temperature oxidation corrosion and inhibits element interdiffusion, forming a dual-barrier synergistic protection structure.

Citation Information

Patent Citations

  • Ti-Al-Si-C coatings modified with carbon nanomaterials on the surface of titanium and titanium alloys and their preparation methods

    CN113430479B